2018
DOI: 10.1039/c8ta01034j
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Cu–TiO2/C nanospheres derived from a Ti precursor encapsulated MOF coating for efficient photocatalytic hydrogen evolution

Abstract: Here we report an effective approach for preparing hollow carbon nanospheres with Cu–TiO2 from a Ti precursor encapsulated surface mounted MOF (SURMOF) coating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…Moreover, the circular (≈ 5 nm) ZnO nanoparticles distribute on surfaces of the solid cubic nanocrystals, as shown in Figure S4c. In contrast to the solid structured ZnO/CN, the hollow nanocages incorporating ZnO and Au nanoparticles could generate more accessible active sites dispersed on the shells, and provide enhanced visible light absorption, which are favorable conditions for an improved photocatalytic performance under the visible light …”
Section: Resultssupporting
confidence: 89%
“…Moreover, the circular (≈ 5 nm) ZnO nanoparticles distribute on surfaces of the solid cubic nanocrystals, as shown in Figure S4c. In contrast to the solid structured ZnO/CN, the hollow nanocages incorporating ZnO and Au nanoparticles could generate more accessible active sites dispersed on the shells, and provide enhanced visible light absorption, which are favorable conditions for an improved photocatalytic performance under the visible light …”
Section: Resultssupporting
confidence: 89%
“…42 Recently, Hao et al demonstrated that when decorated with Pt cocatalyst, Cu-TiO 2 /C hollow nanospheres derived from an external-templated-MOF precursor, SiO 2 / HKUST-1-Ti can be a high performing photocatalyst. 43 Though photocatalytically efficient, to avoid the use of expensive cocatalyst Pt and the complicated multi-step synthetic procedures, the band gap positions of in situ formed heterojunctions, and the physicochemical properties as well as the morphologies of the MOF derived nanocomposites can be effectively adjusted to achieve high performing and stable photocatalysts for H 2 evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the calcined MOF template method, the solvothermal reduction and simultaneous etching of MOFs can better preserve the shape of their shells and avoid the aggregation of cocatalyst, as shown in Figure a,b. Recently, Chen et al synthesized hollow carbon nanospheres encapsulated with Cu–TiO 2 from Ti‐precursor‐coated MOFs (SiO 2 @HKUST‐1 nanospheres) through a liquid‐phase epitaxial step‐by‐step assembly strategy, as shown in Figure c,d. This hollow Cu‐TiO 2 /C not only displayed efficient use of its light source, but also had high photocatalytic activity toward hydrogen production.…”
Section: Design Of Cu‐based Cocatalysts For Photocatalytic Hydrogen Ementioning
confidence: 99%
“…); c) Fabrication process for core‐shell SiO 2 @HKUST‐1 nanospheres using an liquid‐phase epitaxial (LPE) layer by layer assembly approach; d) TEM image; and e) TEM element mapping of C, O, Cu, and Ti in hollow Cu‐TiO 2 /C nanospheres. (Reproduced with permission . Copyright 2016, The Royal Society of Chemistry.…”
Section: Design Of Cu‐based Cocatalysts For Photocatalytic Hydrogen Ementioning
confidence: 99%